Professionalism Enhancement of Ece Tutors Through K13 Learning Devices Production Training In Cibitung Tengah Village, Bogor Regency - Yenina Akmal; Hikmah Hikmah; Ika Subekti; Ichtineza Halida Hardono (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2019)
Abstract - The presence of Early Childhood Education (ECE) tutor in Cibitung Tengah Village Tenjolaya District Bogor Regency is really needed for early childhood in order to become a guide in the ECE institutions. The problem occurred is that the average education level of ECE tutor is diverse, from Middle School, High School, Associate Degree, and Bachelor Degree. In this condition, we can say that those ECE tutors had not had the knowledge and insight about the ECE, namely the 2013 Curriculum, the ECE concept, and the learning devices. Training, along with the research about the role of those training itself, are need to be done in order to answer this question for increasing the knowledge and insight of ECE tutor using action research method. The results showed the enhancement of conducted training, including the enhancement of interest and motivation to develop their knowledge and insight about the ECE. Extended with the existence of WhatsApp group as a platform for communication between ECE tutors and UNJ researchers in the efforts to enhance the professionalism of ECE tutors, in the context of mentoring, ECE Tutors in the Cibitung Tengah, Tenjolaya Village were also involved in the learning devices production training in order to apply the religious moral concept to the ECE in the teaching and learning process at the UNJ and also to observe Ceria Daycare of the Department of ECE, Faculty of Education, UNJ.Keyword - Early Childhood Education (ECE), 2013 Curriculum, Learning Devices